Sikap Masyarakat Terhadap (ODGJ) Orang Dengan Gangguan Jiwa : Analisis Sikap Masyarakat Di Kecamatan Banda Raya Kota Banda Aceh - Maulidiya Agustina; Hijrah Saputra (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2023)
Mental disorder is a condition in which an individual experiences disturbances in behavior, thoughts and feelings that are manifested in a set of symptoms or meaningful behavioral changes, which can cause obstacles and suffering in carrying out human functions. The purpose of this study was to determine what factors are the causes of people with mental disorders and what are the attitudes of the community towards people with mental disorders in the Banda Raya sub-district. The method used in this research is qualitative with a descriptive approach. The results of this study found that the factors causing mental disorders in Banda Raya sub-district Gampong Lamlagang are caused by a combination of several factors, namely biological, sociocultural, and psychological. The attitude shown by the community in the Banda Raya sub-district of Gampong Lamlagang towards people with mental disorders is that some give rejection and some are mediocre but can still accept people with mental disorders.